ANALISIS PENGELOLAAN ANGGARAN DANA BOS TERHADAP AKUNTABILITAS DAN TRANSPARANSI PELAPORAN PERTANGGUNGJAWABAN KEUANGAN SDN 2 GALUNGAN - Mertyani Sari Dewi; Desak Putu Ayu Purma Dewi (STKIP Persada Khatulistiwa Sintang, 2022)
The School Operational Assistance Program is a government policy to support the 9-year compulsory education program. The BOS program funding assistance is intended for school operational costs with the aim of freeing education costs for underprivileged students and easing the burden of students in the future. This study aims to determine the accountability of BOS program fund management at SDN 2 Galungan. The focus of this research is on managing the school operational assistance budget for school financial reporting based on the principles of fairness and efficiency because these two principles are closely related to the stages in school financial management in the planning and budget realization stages. In this study used a qualitative approach with data collection techniques of observation, interviews and documentation. Research informants consisting of: principal, committee chairman, teachers, and school treasurer. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of the study indicate that the accountability of BOS fund management at SDN 2 Galungan in principle has been implemented quite well, although technical problems are still constrained